ISLAMISASI ILMU PENGETAHUAN KONTRIBUSI DALAM MENGATASI KRISIS MASYARAKAT MODERN - Alwi, Marjani (Inspiratif Pendidikan, 2017)
Islamization of science is an attempt to find the root of the problem from the consequences of the concept of dichotomy between religion and science that can be said to be contradictory. Religion assumes or sees a problem from a normative point, whereas science views it from an objective point of view that then becomes one of the causes of the emergence of the crisis of modern society.